Stereochemical Aspects of the C-Glycosylation of Pyranosides and Furanosides - Achanta, Srinivas; Sasikala, Ch. V. A.; Basu, Debjit; Nahide, Pradip D.; Bandichhor, Rakeshwar (Synthesis, 2024)
The stereoselective synthesis of α- and β-C-glycosides is one of the most challenging areas of research in the field of glycoside chemistry. In this review, we summarize the various methods available for stereocontrolled glycosylation and also discuss the predictive models available to explain the stereochemical outcome of six- and five-membered-ring oxocarbenium ions with allyltrimethylsilane nucleophile under Lewis acid conditions.1 Introduction2 Stereochemical Aspects during Glycoside Bond Formation in Pyranosides2.1 Lewis Acid Mediated Nucleophilic Addition to Six-Membered-Ring Oxocarbenium Ions2.2 Arylalane Addition to Anhydroglucose2.3 Glucal Epoxide Method2.4 Glycosyl Leaving Group Substitution Method2.5 Glycosylation via Transition-Metal-Mediated Cross-Coupling3 Stereochemical Aspects during Glycoside Bond Formation in Furanosides3.1 Lewis Acid Mediated Nucleophilic Addition to Five-Membered-Ring Oxocarbenium Ions4 Summary and Conclusion
Keywords: C-glycosylation; stereoelectronic control; transition state; oxocarbenium ion; pyranosides; furanosides